Customer relationship management and information technology as determinants of Malaysian hospitality: A qualitative approach - Hussain, Fawad; Saibu Rahman, Mihraj Begum; Hassan, Mohamad Ghozali (2012)
Today, the hospitality industry is deviating from their traditional way of doing business and is now becoming more customer focused aimed at developing a positive and satisfying relationship with their customers.lnformation technology is the most significant factor that is helping the management of hotel industry to lower costs, increase operational excellences with profitability slid give value to customer's time.Malaysian hospitality industry is based on Malaysian customer, culture involving a specific way of treating customers.The competitive advantage in this industry is based on the time and cost factors, which worries the customer and the hotel management.lnformation technology has helped the entire industry to prevent the wastage of resources and time by fulfilling optimum customer needs and demands.This paper is an attempt to explore the customer relationship management and IT related issues in three star rated hotels in the state of Penang, Malaysia.This paper would contribute as a useful guide to three star hotels, giving them some valuable information on what the customer expectations arc in terms of CRM and IT facilities and if they are duly met then services and operational issues shall not occur.The significance of this case study includes providing a scope for three star rating hotels to improve their IT based activities to influence service quality and reduce the weaknesses, through availing opportunities and to strengthen their position in the industry.